(untitled) (International journal of artificial intelligence, 2026)
This article presents a comprehensive scientific analysis of the regional economic development of the Bukhara region of Uzbekistan, focusing on the structural features, resource dependence, and emerging transformation processes shaping its growth trajectory. The study examines the historical foundations of the regional economy, the dominant role of the energy and agricultural sectors, and the challenges associated with environmental degradation and innovation gaps. Particular attention is given to the prospects of economic diversification through digitalization, tourism development, and renewable energy adoption. The analysis demonstrates that while the Bukhara region possesses substantial economic potential, its long-term sustainable development requires a strategic transition from a resource-based model toward a diversified, innovation-driven, and environmentally sustainable regional economy.